2014
DOI: 10.1121/1.4887447
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling sound-source localization in sagittal planes for human listeners

Abstract: Monaural spectral features are important for human sound-source localization in sagittal planes, including front-back discrimination and elevation perception. These directional features result from the acoustic filtering of incoming sounds by the listener's morphology and are described by listener-specific head-related transfer functions (HRTFs). This article proposes a probabilistic, functional model of sagittal-plane localization that is based on human listeners' HRTFs. The model approximates spectral audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
180
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(185 citation statements)
references
References 42 publications
4
180
1
Order By: Relevance
“…Initially we intended to manipulate the salience of monaural spectral shape cues that are arguably most important for sound localization within a sagittal plane (34). Monaural loudness predictions, however, revealed that smaller spectral contrasts were accompanied by a decrease in loudness at low and mid frequencies and an increase in loudness at high frequencies.…”
Section: Spectral Contrast Manipulation Affected Auditory Distance Pementioning
confidence: 99%
“…Initially we intended to manipulate the salience of monaural spectral shape cues that are arguably most important for sound localization within a sagittal plane (34). Monaural loudness predictions, however, revealed that smaller spectral contrasts were accompanied by a decrease in loudness at low and mid frequencies and an increase in loudness at high frequencies.…”
Section: Spectral Contrast Manipulation Affected Auditory Distance Pementioning
confidence: 99%
“…Since HRTFs vary substantially across listeners [11], the spectral mismatch also varies from case to case. Psychoacoustic localization experiments showed that amplitude panning in the median plane might work for some unspecified listeners, but a derivation of a general rule holding for all listeners has not been achieved [2].In this study we aim at a more systematic and objective investigation of the limitations of VBAP by applying a model of sagittal-plane sound localization for human listeners [12]. This model has been extensively evaluated in previous studies [12,13].…”
mentioning
confidence: 99%
“…Note that in contrast to [22], who used absolute spectral average, our spectral distortion was based on standard deviation in order to obtain a metric robust against the confounding effect of broadband differences between HRTFs. Also note that the model from [4], while showing good predictive power for normal-hearing listeners, was not applied in our study because it has neither been calibrated nor applied to hearingimpaired listeners yet. Finally, pairs of conditions were compared by means of the spatial correlation analysis [23].…”
Section: Hrtf Evaluationmentioning
confidence: 99%
“…HRTFs can be used for many purposes, e.g., for models of spatial hearing [4][5][6], for fitting of hearing aids [7,8], and for presenting virtual binaural audio signals via headphones in socalled virtual auditory displays [9,10]. As HRTFs depend on the individual geometry of the listener's head and ear, HRTFs are listener-specific [11].…”
Section: Introductionmentioning
confidence: 99%